Retreatment of multiple failing maxillary implants after full arch rehabilitation: a retrospective, observational cohort study. Issue 11 (November 2020) - Onclin, P.; Meijer, H.J.A.; van Minnen, B.; Vissink, A.; Raghoebar, G.M.
Abstract: The aim of this study was to assess implant retreatment in a group of patients whose maxillary implants were all failing after full arch rehabilitation. Treatment involved implant removal, augmentation, and placement of an overdenture supported by four to six implants. All consecutive patients referred between 2008 and 2018, following multiple late implant failures in the rehabilitated maxilla, were included in the study. Seventy implants in 15 patients were evaluated at 3.3 ± 2.5 years (range 1.1–8.6 years) after loading. Implant survival, complications, clinical parameters, marginal bone loss, and patient-related outcome measures were recorded at the time of evaluation. Overall implant survival was 95.7%. Three implant failures occurred within the first year of function. Marginal bone loss was 0.32 ± 0.46 mm; pocket probing depth was 4.55 ± 1.59 mm. Plaque, calculus, inflammation, and bleeding were hardly seen (median index score 0). Patients scored their satisfaction with their overdentures as high (mean overall score 8.7 ± 1.2, maximum 10). Chewing soft and tough food was scored as 'good' and hard food as 'moderate'. The mean Oral Health Impact Profile score was 29.5 ± 33.3. It can be concluded that the replacement of multiple failing implants in an edentulous maxilla after bone augmentation is a safe and predictable treatment procedure when applied as an implant-supported overdenture.